Pest management in mango by farmers of Central Gujarat (Indian Journal of Arid Horticulture, 2025)
Mango (Mangifera indica L.) nicknamed as king of fruits in India is the major fruit crop. It tops the list of preference of farming community for cultivation due to endless demand in domestic as well as international market. Mango cultivar 'Kesar' is one of the finest delicacies from Gujarat exported to Europe. In the package of practices of cultivation of mango to be followed by the farmers plant protection occupies a significant role. Negligence of this aspect brings about considerable loss of yield and quality. Mango malformation is still an unsolved mystery. Many insects and fungal pathogens attack mango. Keeping this in view, a survey was conducted to assess the adoption level of pest management in mango by the farmers of Central Gujarat.
Keywords: salient cause; pathogens